Reconstruction of a complex lower leg defect following oncologic resection with a combination of inferiorly based peroneus brevis muscle flap and fasciocutaneous flaps: a case report - Boro, Sumanjit S.; Sahewalla, Ashutosh; Talukdar , Abhijit (International Journal of Research in Medical Sciences, 2024)
Wounds and soft tissue defects in the distal third of the leg and ankle remain a challenge. Defects at this site will often require a flap cover. A free flap is an ideal choice for these defects but it has its limitations. The distal peroneus brevis muscle flap is a well-described flap for such defects. Peroneus brevis is an expendable muscle in the leg without much functional deficit. A 38-year-old male patient presented with a chronic ulcer in the right leg for 1year of which biopsy was positive for squamous cell carcinoma that underwent wide local excision with peroneus brevis flap reconstruction and also two local fasciocutaneous flaps. The distally based pedicled peroneus brevis muscle flap is an economical, reliable, and relatively easy procedure for treating defects of the heel, Achilles tendon, and medial and lateral malleolus, extending deep into the ankle.